a) \({\cos ^2}\frac{\pi }{8} + {\cos ^2}\frac{{3\pi }}{8} = {\cos ^2}\frac{\pi }{8} + {\cos ^2}\left( {\frac{\pi }{2} - \frac{\pi }{8}} \right) = {\cos ^2}\frac{\pi }{8} + {\sin ^2}\frac{\pi }{8} = 1\)
b)
\(\begin{array}{l}\tan {1^ \circ }.\tan {2^ \circ }.\tan {45^ \circ }.\tan {88^ \circ }.\tan {89^ \circ }\\ = (\tan {1^ \circ }.\tan {89^ \circ }).(\tan {2^ \circ }.\tan {88^ \circ }).\tan {45^ \circ }\\ = (\tan {1^ \circ }.\cot {1^ \circ }).(\tan {2^ \circ }.\cot {2^ \circ }).\tan {45^ \circ }\\ = 1\end{array}\)